الشيخ عبد الله بن فودي النيجيريّ وموقفه من التصوّف: Shiekh Abdullah Bin Fũdi, al- Nayjĩri: His Stand on Sufism - Abdur Razzaq, Alawiye Abdul Mumin; Mokhtar, Ahmad Wifaq; Ismail, Abdul Manan; Hasbullah, Mushaddad; Yusuf, Shittu Bilal (‘Abqari Journal, 2018)
This paper is to clarify the stand of Ibn Fũdi on Sufism. He emerged as one of the scholars during the nineteenth century, as a result of a great portion of knowledge given to him by Allah. The researchers used inductive, deductive and analytical methods. Meanwhile, this paper comprises three sections after the introduction. The first section treats the biography of Ibn Fudi. The second deals with his opinions on Sufism, while the third analyses his opinions and the general perspectives on Sufism. Finally, it is realised that Ibn Fudi was a scholar who used to follow the Islamic guidelines in his activities and frowned against all unconventional acts of the Sufi order. Keywords: Ibn Fũdi, sufism and stand. الملخّص تستهدف هذه المقالة بلورة موقف الشيخ ابن فودي من التصوّف. كان ابن فودي أحد علماء القرن التاسع عشر الميلادي. تمّ استخدام المنهج الاستقرائيّ والمنهج الاستنباطيّ ومنهج الوصف التحليليّ؛ جمعا للمعلومات عن ترجمة الشيخ واستقصاء لآراء ابن فودي وغيره من العلماء مع تحليل النكتات المنوطة بالتصوّف. تتكوّن الدراسة من التمهيد ومباحث ثلاثة ثمّ الخاتمة. فالمبحث الأوّل عبارة عن مؤجز الترجمة لابن فودي؛ وحين ينصبّ الثاني على عرض فتواه وآرائه حول التصوّف، يُعنى المبحث الأخير بدراسة تحليلية لآرائه في التصوّف. والخاتمة عبارة عن النتائج. لقد تتج عن هذه الدراسة معرفة موقف ابن فودي؛ كان عالما متصوّفا ملتزما بالتوجيهات الإسلاميّة في حركاته، مما يدلّ على أنّه قد أنكر الشطحات الصوفيّة. الكلمات المفتاحيّة: ابن فودي، موقف، التصوّف.